(3dGejI GdYQHs - (3GdTfaQj Hf GdGhS Hf GdMLQs ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3CbjehG Hfi ai UOhQ eWje aEfi Edi bhe ShGce dGejd s
(3BNQgG (B:s
(3hjQcV HGdCUGd Mhdi cCffi ef GdYUe COai jfJMi GdcjM CYbd JeJ GdefXheI GdeSeGg HdGejI GdYQH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs